Impact of Green HRM practices on employees and their performance - Chauhan, Priyam (2019)
Employee performance Management is becoming important for an organization day by day as the organisation has to go through various changes occurring in the environment. In the present scenario organizations are focusing on applying green techniques in the company in order to contribute towards the sustainable environment. Organizations are emphasizing on measuring the impact of green HRM policies on the employee performance level. The successful delivery of these practices and techniques depends upon the employee participation.